Morte da arte?: O tema do fim da arte nos Cursos de estética de Hegel - Katia Silva Araujo (2006)
The scope of this dissertation is based on two hypotheses to sketch an investigation about the end of arts issued in Hegels work. The first hypothesis points towards a systematic end of art in the triad of Absolute Spirit, that is, other spiritual manifestations under a conceptual form, such as religion and philosophy take the place that once had belonged to the arts. The second hypothesis discusses about the systematic intention of the Esthetics. The first step is to consider the successive artistic expressions pointed by the philosopher under a symbolic, classic and romantic form. The second one is to consider the specific form of arts, such as architecture, sculpture, painting, music and poetry according to a historical line. So, we have concluded that it is necessary, for these questions, to depart from Hegels concept of art, because it leads to the understanding of the philosophers systematic intension: the end of art. The end of art concept is finally explained as an assumed resurrection, which means, the death of this subject. Comparing the first concept with the Esthetics questions, the end of art is actually the end of the true ideal. Looking at the history of art, its purposes such aspresented by Hegel, do not suggest a pessimistic attitude beyond the studies of art. Even though it is considered the idea of the prosiest of the modern world, but it is certainly an optimist end, as the philosopher conceives the dialectic system.